Hubungan antara kecerdasan emosi dengan konsep kendiri dalam kalangan ibu tunggal tidak bekerja di Johor Bharu - Remeo, Helena (2014)
The purpose of this study is to investigate the relationship between emotional intelligence dimensions of emotional stability in the self-concept of non-working single mothers in Johor Single Mothers Association (CARE) in terms of self-identity (ID), self satisfaction (KK), Self behavior (TK), physical self (KF), Personal Self (SF), the ethics and moral self (CAMP), family self (KKG) and social self (KS). This study uses the Survey Tool Bar-On EQ 360 (Bar-On, 1997) and the Tennessee Self-Concept Questionnaire (Fitts, 1965). It is a research tool that has been translated into English by previous researchers. The data were analyzed using SPSS version 14.0 with descriptive statistical method. The data were analyzed by using this frequency, percentage, and mean. Pearson correlation analysis method was used to analyze the relationship between emotional intelligence and self-concept and self-concept dimensions among non-working single mothers in Johor Bharu. In this study there are a number of theories and models of emotional intelligence-related and consistent with emotional intelligence (EQ) studied the Theory of Multiple Intelligences, The Theory of Success Intelligence and The Emotional Learning System Theories and models are involved in the self-concept is about Maslow's Needs Theory, Theory of Individual Centering Theory Carl Rogers and Karen Horney. The findings show the majority of single mothers have high levels of emotional intelligence and high self-concept. All self-concept except KF has a significant relationship with emotional intelligence. The study also made to study the independent variables (predictors) in the highest regression model contributed to the change in the single mother's emotional intelligence self-concept of physical self (KF) because it was statistically significant in the regression equation in which the dimension of value t = 5369, p = 0.000. In conclusion, most of the research supports a number of past studies. The results of this study will hopefully help non-working single mothers in the state of Johor in raising the level of emotional intelligence and self-concept in leading their daily life.